ALGORITMA MODULAR UNTUK SISTEM PROSES DENGAN RECYCLE - KEADAAN TUNAK PADA PERANGKAT LUNAK BEBAS BIAYA LISENSI - Setia Budi Sasongko (Reaktor, 2008)
Computer simulasion can be developed to comprehend a system process characteristic and can be used to train the operator of process. The first problem of programming is high price of the licence. Using the FOC (free of charge) software solve of the previous problem such as Scilab and Open Office which comparable with Matlab and Excel. The objectives of this article develop process system programming which has recycle system and user friendly programming. Modular algorithm programming is introduced to solve recycle process system. Graphical User Interface (GUI) also introduces to make user friendly programming. Execution of the program performs stable and correct results.